Understanding the dynamics of air pollution during forest fires in Antalya-Manavgat: A WRF-CHEM analysis - Kara, Yiğitalp (Graduate School, 2024)
This thesis aims to investigate the air pollution dynamics of the Antalya Manavgat forest fires in Turkey, utilizing the advanced Weather Research and Forecasting model coupled with Chemistry (WRF-Chem) and the Fire INventory from NCAR version 2.5 (FINN v2.5) boundary fire emission data. The research is dedicated to comprehensively understanding both the synoptic and microscale atmospheric conditions that prevailed during the forest fire events, delving into the complexities of meteorological influences on fire behavior and pollutant distribution. A key aspect of our investigation is examining the influence of the Foehn effect, a dry and warm down-slope wind, on intensifying the initial fire conditions which may exacerbate fire spread and severity. This phenomenon is critical as it can significantly modify the local weather conditions and thereby affect the behavior of the fire and the resultant air quality issues. Furthermore, the thesis rigorously assesses the performance of the WRF-Chem model in accurately predicting essential atmospheric parameters such as Aerosol Optical Depth (AOD), Aerosol Absorption Index (AAI), Particulate Matter (PM₁₀), and various meteorological variables. The analysis of atmospheric conditions during the Manavgat forest fires in Antalya between July 26 and August 9, 2021, revealed several key findings. The Weather Research and Forecasting model coupled with Chemistry (WRF-Chem) is a state-of-the-art atmospheric modeling system utilized for simulating the interactions between meteorology and atmospheric chemistry. With options for two domains, spanning varying resolutions from 9×9 km to 3×3 km, and employing 50 vertical levels, WRF-Chem offers detailed insights into atmospheric processes. Meteorological boundary conditions are derived from ECMWF ERA5 Reanalysis data, supplemented by sea surface temperature data from the same source. Cloud microphysics are parameterized using the WSM6 scheme, while boundary layer dynamics are modeled using the MYJ scheme. The representation of cumulus clouds follows the Grell-3 scheme, and radiative processes are accounted for with the RRTMG scheme for both longwave and shortwave radiation. The land surface is modeled using the Noah-MP scheme, while the surface layer incorporates the Eta Similarity scheme.
Antalya-Manavgat'ta orman yangınlarında hava kirliliğinin dinamiklerini anlamak: WRF-CHEM analizi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: air pollution; hava kirliliği; micrometeorology; mikrometeoroloji; forest fires; orman yangınları